Kesadaran Akan Keberdosaan Dalam Mazmur 130 dan Relevansinya Dalam Penghayatan Sakramen Tobat Masa Kini - Kapitan, Jufrianus; Boy, Mikhael Valens; Senda, Siprianus Soleman (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The awareness of the sinfulness of the people today is very minimal. This has led to less participation in the celebration of the sacrament of penance. This paper is a paper that elaborates on the importance of awareness of guilt and sin.  The book of Psalms 130 becomes a reference so that people can understand the importance of awareness of sin and get forgiveness because of God's faithful love for humans. The research method used is qualitative method or literature study. By using this method, this paper can help the faithful to realize sin and the importance of the sacrament of penance in life to restore the relationship with God.